The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1038/labinvest.3780211
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Proline-Rich Kinase Pyk2 Expression Correlate with Prostate Cancer Progression

Abstract: SUMMARY:Proline-rich kinase 2 (Pyk2), also known as CAK␤ (cell adhesion kinase ␤), is a cytoplasmic tyrosine kinase that is structurally related to focal adhesion kinase. Pyk2 is expressed in different cell types including brain cells, fibroblasts, platelets, and other hemopoietic cells. Pyk2 is rapidly tyrosine phosphorylated in response to diverse extracellular signals acting via different post receptor pathways. We have investigated whether this protein kinase is functionally expressed in normal and neoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 57 publications
1
40
1
Order By: Relevance
“…Stanzione and coworkers first reported the expression of PYK2 in benign and malignant prostate tissues (Stanzione et al 2001). However, in contrast to our observations, Stanzione's works showed that PYK2 is expressed only in benign prostate tissues, whereas its expression progressively reduces with an increasing grade of malignancy of PCa.…”
Section: :8contrasting
confidence: 55%
“…Stanzione and coworkers first reported the expression of PYK2 in benign and malignant prostate tissues (Stanzione et al 2001). However, in contrast to our observations, Stanzione's works showed that PYK2 is expressed only in benign prostate tissues, whereas its expression progressively reduces with an increasing grade of malignancy of PCa.…”
Section: :8contrasting
confidence: 55%
“…41 In contrast, other studies reported rather decreased Pyk2 expression in advanced osteosacroma 42 and in high-grade prostate cancer compared with normal epithelial prostate tissue and benign prostatic hyperplasia. 23 These reports used small numbers of tissue cases and did not address the context of overexpression of the prognostic marker ErbB-2.…”
Section: Discussionmentioning
confidence: 99%
“…PYK2 thus seems to have multiple ways to mediate ARA55-enhanced AR transcriptional activity. PYK2 is expressed in neurons, bone marrow, smooth muscles, and prostate (79,80). Tissue staining showed that PYK2 was decreased with increased malignancy of prostate cancers (80), indicating a regulatory role of PYK2 on ARA55-enhanced AR-mediated growth of cancer cells.…”
Section: Ar Coactivators In Prostate Cancermentioning
confidence: 99%